Correlation of total phenolic and flavonoid contents on the antioxidant activity of Psychotria gitingensis and Psychotria pilosella - Aureada, Mikaela Yakira M.; Duran, Jo Dexter R.; Falcatan, Stephanie Rafaelle A.; Pornillos, Kirsten Marla T.; Villanueva, Mary Angela G.; Ordas, Jorge Anton D.; Tan, Mario A. (Journal of Phytology, 2023)
The genus Psychotria (Rubiaceae) possesses various biological properties, ranging from phytochemical and pharmacological properties of their chemical constituents to traditional medical applications. Most Psychotria species remain unstudied despite high diversity and endemism in the Philippines. Hence, this study investigates the total phenolic and flavonoid contents of Psychotria gitingensis and Psychotria pilosella methanolic crude extracts, evaluates their antioxidant properties, and assesses their antibacterial properties. Results revealed that P. gitingensis fruit extract exhibited the highest phenolic content (254.45 ± 6.63 mg GAE/g extract) and flavonoid content (9.85 ± 0.49 mg QE/g). In addition, it also displayed the highest antioxidant activity (0.993 ± 0.041 mg/mg) in the ABTS assay. P. pilosella leaf extract exhibited the highest antioxidant activity in DPPH (70.53% ± 1.50), and P. gitingensis leaf extract showed the highest iron-reducing antioxidant power (86.06% ± 0.73) in FRAP. Paper disk diffusion tests, however, did not exhibit activity against selected nosocomial pathogens. The results of this study contribute to expanding the field of knowledge on alternative treatments and paving the way for the development of new medicinal products.